2010
DOI: 10.1007/s10482-010-9481-x
|View full text |Cite
|
Sign up to set email alerts
|

Changes to the rumen bacterial population of sheep with the addition of 2,4,6-trinitrotoluene to their diet

Abstract: Previous work has shown that bacterial isolates from the sheep rumen are capable of detoxifying 2,4,6-trinitrotoluene (TNT) into polar constituents. In this study, the dietary effects of TNT on the sheep rumen microbial community were evaluated using molecular microbiology ecology tools. Rumen samples were collected from sheep fed with and without TNT added to their diet, genomic DNA was extracted, and the 16S rRNA-V3 gene marker was used to quantify changes in the microbial population in the rumen. Control an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 50 publications
5
12
0
3
Order By: Relevance
“…These results correlate well with the other published research that has characterized the rumen using the 16S-based gene marker [16,30,38,43]. Evaluations of ruminal microbial communities in cattle [16,38,43], sheep [24,31] and some wild ruminants [4,28] have shown them to be dominated by low GC Gram-positive bacteria (LGCGPB), particularly those related to the broad genus Clostridium.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…These results correlate well with the other published research that has characterized the rumen using the 16S-based gene marker [16,30,38,43]. Evaluations of ruminal microbial communities in cattle [16,38,43], sheep [24,31] and some wild ruminants [4,28] have shown them to be dominated by low GC Gram-positive bacteria (LGCGPB), particularly those related to the broad genus Clostridium.…”
Section: Resultssupporting
confidence: 88%
“…Although ruminants consume forage as primary mode of nutrition, they possess diverse microflora that has been used to help detoxify several plant toxins such as pyrrolizidine alkaloid (PA) [32], oxalate [3], nitropropanol [5], dihydroxypyridine [13], and munition such as TNT [12,31] and RDX [15].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cunha et al (2011) studied the rumen microbiome community structure in goats from the semiarid region of Brazil and concluded that the proportions of Firmicutes and Bacteroidetes present in the rumen liquid were 56.3% and 37.9%, respectively. In those sheep fed a grass hay or alfalfa mixture, the predominant microbial communities belonged to Firmicutes (approximately 44-45%) and Bacteroidetes (about 43%) (Koike et al, 2004;Perumbakkam et al, 2011). However, in dairy sheep fed marine algae, changes due to the addition of marine algae to the diet were observed, and the proportions of Firmicutes and Bacteroidetes were 13-26% and 69-77%, respectively (Castro-Carrera et al, 2014;Chaucheyras-Durand and Ossa, 2014).…”
Section: Discussionmentioning
confidence: 98%
“…This observation is consistent with the current study in that no MTBE biodegradation under the sulfate-and nitrate-amended conditions (no methane was produced), although they were seeded from the same inocula. Ruminococcaceae were also linked with 2,4,6-trinitrotoluene (TNT) degradation in a recent study (42).…”
Section: Figmentioning
confidence: 98%